‘Peacefully’ at ‘War’: An Analysis of the Southern African Development Community’s Institutional Framework’s Failure to Respond Adequately to the Ongoing Conflict in Swaziland - Nhlabatsi, Sibusiso (South African Yearbook of International Law)
The Kingdom of Swaziland is well known for being a peaceful nation. This historical claim is supported by the fact that the little kingdom is situated between two nations that at some point engaged in armed conflict, the Republic of South Africa and the Republic of Mozambique. When tensions in the two states mentioned above were at their worst, Swaziland served as a haven for those fleeing the violence. However, the little kingdom has recently been embroiled in internal conflict as demands for democratic reforms grow, and the King rebuffs attempts to overthrow his absolute authority. The Southern African Development Community (SADC) framework for resolving regional conflicts is analysed in this article, together with the ongoing conflict in the Kingdom of Swaziland. The many fact-finding missions and SADC organs’ visits to Swaziland are discussed in this article, along with how their inaction is sustaining a protracted, intense internal conflict. The study also looks at the role that state-sponsored terrorism has played in the response to the conflict by His Majesty King Mswati III's administration. The tiny kingdom is at a turning point because SADC has failed to impose its authority and because the King, despite his undertaking, has actively avoided political engagement. Furthermore, the study argues that the protracted violence in Swaziland will have detrimental effects on South Africa, which already has a fragile economy and is trying to manage the refugee surge. It concludes by positing that it would be ideal to prevent a dangerous scenario for the region if SADC intervened by asserting its authority and demanding a proper dialogue in Swaziland among all stakeholders with clear terms of reference.